2018
DOI: 10.7554/elife.39151
|View full text |Cite
|
Sign up to set email alerts
|

The fate of hippocampal synapses depends on the sequence of plasticity-inducing events

Abstract: Synapses change their strength in response to specific activity patterns. This functional plasticity is assumed to be the brain’s primary mechanism for information storage. We used optogenetic stimulation of rat hippocampal slice cultures to induce long-term potentiation (LTP), long-term depression (LTD), or both forms of plasticity in sequence. Two-photon imaging of spine calcium signals allowed us to identify stimulated synapses and to follow their fate for the next 7 days. We found that plasticity-inducing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Neuroarchitectural changes would provide a substrate for the construction of longer-term dynamic memory support with repeated spaced training. A distinction between transient functional changes and more enduring structural changes with LTP has A B1 B2 recently been proposed in another model plasticity system (Wiegert et al 2018). The week-old rat pup OB offers a highly tractable model for illuminating the biology of mammalian learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroarchitectural changes would provide a substrate for the construction of longer-term dynamic memory support with repeated spaced training. A distinction between transient functional changes and more enduring structural changes with LTP has A B1 B2 recently been proposed in another model plasticity system (Wiegert et al 2018). The week-old rat pup OB offers a highly tractable model for illuminating the biology of mammalian learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…LTP is thought to result from faciliatory stimulation protocols, such as 10 Hz rTMS, whereas LTD seems to result from inhibitory protocols, such as cTBS. A recently published study ( Wiegert et al, 2018 ) showed that optogenetically induced LTP in rat hippocampus enhances synaptic stability over days, whereas long-term depression (LTD) destabilizes synapses. Most potentiated synapses are resistant to depression suggesting that synaptic transmission strength depends on the sequence of plasticity-inducing stimulations ( Wiegert et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study ( Wiegert et al, 2018 ) showed that optogenetically induced LTP in rat hippocampus enhances synaptic stability over days, whereas long-term depression (LTD) destabilizes synapses. Most potentiated synapses are resistant to depression suggesting that synaptic transmission strength depends on the sequence of plasticity-inducing stimulations ( Wiegert et al, 2018 ). High stimulation load induced by multiple rTMS/tDCS sessions may enhance the stabilizing effect on synaptic transmission in stimulated cortical areas, such as the DLPFC, with potentially larger effects on corresponding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of excitatory synapses on neuronal dendrites are located on small membranous protrusions called dendritic spines. Spines are highly dynamic structures that can undergo extensive morphological changes, appear, disappear or become stabilized over long periods of time (weeks and months), depending on the type of synaptic input they receive (Wiegert et al, 2018). The structural plasticity of dendritic spines depends on the tight regulation of spinous Ca 2+ -signaling, and on local, activity-dependent protein and membrane turnover.…”
Section: Introductionmentioning
confidence: 99%